2022
DOI: 10.1111/bjet.13285
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cognitive presence in online inquiry‐based discussion through text classification and epistemic network analysis

Abstract: Providing coaching to participants in inquiry‐based online discussions contributes to developing cognitive presence (CP) and higher‐order thinking. However, a primary issue limiting quality and timely coaching is instructors' lack of tools to efficiently identify CP phases in massive discussion transcripts and effectively assess learners' cognitive development. This study examined a computational approach integrating text mining and co‐occurrence analysis for assessing CP and cognitive development in online di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Sun and Theussen (2022) applied social network analysis to dynamically assess the development of students' negotiation skills and demonstrated that complexity of negotiation skills was positively related to negotiation outcome in a collaborative simulation game. Ba et al (2022) developed text classifiers to detect phases in cognitive presence and then used epistemic network analysis to identify cognitive patterns in student online discussion transcripts. Temporal and fine-grained analytics approaches presented in this study may be a promising venue towards advancing dynamic and theory-aligned assessments of computer-supported collaborative learning.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…Sun and Theussen (2022) applied social network analysis to dynamically assess the development of students' negotiation skills and demonstrated that complexity of negotiation skills was positively related to negotiation outcome in a collaborative simulation game. Ba et al (2022) developed text classifiers to detect phases in cognitive presence and then used epistemic network analysis to identify cognitive patterns in student online discussion transcripts. Temporal and fine-grained analytics approaches presented in this study may be a promising venue towards advancing dynamic and theory-aligned assessments of computer-supported collaborative learning.…”
Section: Brief Overview Of Contributionsmentioning
confidence: 99%
“…ENA has great potential to understand the development of students’ CT in collaborative programming. ENA can effectively detect differences in connections between codes with similar frequencies compared with automated content analysis (Ba et al, 2022) and quantitative content analysis (Csanadi et al, 2018). It also goes beyond traditional static quantitative analysis to capture progressive relationships between different variables, such as cognition and interaction (Guo et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Epistemic Network Analysis (ENA) is a discourse analysis method. Due to its ability to reveal the interaction, support, and temporal process in the collaboration (Zhang et al, 2022), ENA has been used in many studies to understand the development trajectory of learners’ ideas in scientific creativity tasks (Sun et al, 2022), higher-order thinking (Ba et al, 2022), metacognitive patterns (Wu et al, 2020), social-cognitive engagement (Ouyang et al, 2022), and even to compare metacognitive differences between low- and high-scoring groups (Wu et al, 2020; Zhang et al, 2019). ENA can model the connections between features of student dialogue by quantifying their co-occurrences in the dialogue, and thus produce a weighted network of co-occurrences and visualizations linked with each data analytical component.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations